2021
DOI: 10.30599/jipfri.v5i1.852
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kemampuan Self Regulation Siswa pada Pembelajaran Sains saat PJJ Online di Era Pandemi Covid-19

Abstract: This study aims to determine students' self regulation  during the Covid-19 pandemic at islamic senior high school in Kabupaten Karawang, West Java. The research method used  descriptive method and data collection techniques using a survey through Google Form. The research subjects were Grade X,XI,XII . The results showed that the skill of students’ self regulation was in the high category with presentage of 17%, medium category 69% and high catogory 14%. Based on three components of self-regulation, majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Ellianawati et al (2021) argued that during the Covid-19 pandemic, the decline in learning outcomes could also be influenced by the learning process in the classroom and students' motivation. In the learning process during the Covid-19 pandemic, students and teachers are required to carry out online and offline learning processes (Setyaningrum et al, 2021;Koeswanti, 2021;Agung et al, 2022). In practice, when conducting an online learning process, most teachers only send teaching materials in the form of PDF files to class groups, while in offline learning, they apply an emergency curriculum, where learning hours are cut so that they cannot do practical work in the laboratory (Sukarno & Widdah, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ellianawati et al (2021) argued that during the Covid-19 pandemic, the decline in learning outcomes could also be influenced by the learning process in the classroom and students' motivation. In the learning process during the Covid-19 pandemic, students and teachers are required to carry out online and offline learning processes (Setyaningrum et al, 2021;Koeswanti, 2021;Agung et al, 2022). In practice, when conducting an online learning process, most teachers only send teaching materials in the form of PDF files to class groups, while in offline learning, they apply an emergency curriculum, where learning hours are cut so that they cannot do practical work in the laboratory (Sukarno & Widdah, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has caused changes in all aspects of life, one of which is education. Setyaningrum et al (2021) revealed that the COVID-19 pandemic currently being faced has also changed the world of education, starting from the curriculum, learning process, assessment system, and supporting infrastructure to the education budget. Learning is carried out online with a remote system between teachers and students.…”
Section: Introductionmentioning
confidence: 99%